Gel battery cell and preparation method and application thereof

By performing in-situ anion polymerization on the surface of the negative electrode of the lithium battery, a gel polymer electrolyte and a stable SEI layer are formed, which solves the safety hazards and electrochemical performance attenuation of lithium batteries, and achieves higher electrochemical performance and longer Service life.

CN119230929APending Publication Date: 2024-12-31CHINA FAW CO LTD

Patent Information

Application Number
CN202411145780.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Traditional lithium batteries have safety hazards for organic electrolytes that are easy to volatile and leak easily. The ionic conductivity of polymer solid electrolytes is low, and it is difficult to commercially apply. The SEI film layer lacks elasticity and cannot adapt to the volume changes of the negative electrode, resulting in electrochemical performance degradation. .

Method used

Using a non-toxic and safe in-situ anion polymerization method, the gel polymer electrolyte is formed on the surface of the negative electrode using electron-deficient double bond monomer and crosslinking agent to form a stable inner inorganic SEI layer, reducing interface side reactions and enhancing the interface stability of the negative electrode and the electrolyte is fixed by gel electrolyte, reducing leakage and volatility.

Benefits of technology

It improves the safety and cycle stability of lithium batteries, extends the battery life, improves electrochemical performance and safety, has a capacity retention rate of 96%, reduces the interface contact impedance, and enhances the lithium ion transfer efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005002147170000011
    Figure FDA0005002147170000011
  • Figure FDA0005002147170000012
    Figure FDA0005002147170000012
Patent Text Reader

Abstract

The invention provides a gel battery cell as well as a preparation method and application thereof, and relates to the technical field of secondary batteries. Specifically, the gel cell comprises a positive electrode, a negative electrode and a gel polymer electrolyte, and the gel polymer electrolyte comprises a polymer and an electrolyte; wherein the polymer is prepared by carrying out in-situ polymerization on an electron-deficient double-bond monomer and a cross-linking agent on the surface of the negative electrode, and the electron-deficient double-bond monomer is an acrylate compound containing a specific functional group. The polymer protection layer is formed on the surface of the negative electrode through the in-situ anionic polymerization reaction, and the polymer further reacts with the negative electrode to form the stable inorganic SEI film layer, so that the battery rate capability is improved while the interface stability of the electrolyte and the negative electrode is improved; the electrolyte is fixed in a polymer network by a gel network formed by the gel polymer electrolyte, so that the side reaction of an interface is reduced, the service life of a battery cell is prolonged, and the gel polymer electrolyte has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a gel battery cell and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in life due to their advantages such as high energy density, low self-discharge rate and long cycle life. In recent years, people's pursuit of more environmentally friendly and greener travel methods has led to the rapid development of new energy electric vehicles, and at the same time, higher requirements have been placed on lithium batteries with high energy density and high power density. However, traditional lithium batteries use volatile and leaky organic electrolytes, which pose safety hazards of combustion or even explosion in the event of accidents such as collisions. The unstable interface between the electrode and the electrolyte will lead to the intensification of interface side reactions, the thickening of the interface layer, and the increase of interface impedance, which will lead to continuous attenuation of electrochemical performance. The active and violently expanded negative electrode will cause the electrolyte to continue to decompose at the interface, consume the electrolyte and active lithium ions, and make the interface film layer SEI continue to thicken, which will cause the battery internal resistance to continue to increase and the reversible capacity to decrease. In addition, lithium batteries with graphite, lithium metal as the negative electrode or without a negative electrode may form lithium dendrites and dead lithium during the cycle process, which not only damages the electrochemical performance of the lithium battery, but also brings huge safety hazards.

[0003] Polymer solid electrolytes have the advantages of being non-volatile and non-leaking, and can effectively solve the safety hazards of liquid electrolytes such as high fluidity and easy leakage. However, polymer electrolytes rely on the transfer of lithium ions between polymer chains. Affected by the flexibility of the intrinsic polymer chains, the room temperature ionic conductivity is low, making commercial applications difficult. Combining the advantages of polymer solid electrolytes and liquid electrolytes, polymer gel electrolytes can reduce the leakage and volatilization of electrolytes while ensuring ion conductivity, thereby improving battery safety. If an in-situ polymerization method is used, the interfacial transfer impedance can be further reduced; however, in-situ polymerization usually requires harsh initiation conditions or the addition of toxic initiators, and further development of simple, effective, non-toxic and safe initiation methods is needed.

[0004] In the prior art, additives can be added to the electrolyte to enhance the interfacial stability between the electrolyte and the negative electrode, reduce the decomposition of the electrolyte and improve the coulombic efficiency of the battery; at the same time, by balancing the lithium deposition and stripping process on the negative electrode surface, the migration and diffusion of lithium ions in the electrolyte and the negative electrode surface are promoted, the lithium precipitation process is reduced or even inhibited, and the cycle stability and safety of the lithium battery are improved. Although there are various types of lithium salt additives in the electrolyte, the SEI film layer formed lacks elasticity and cannot adapt to the volume expansion and contraction of the negative electrode during the cycle, which still leads to the attenuation of the electrochemical performance of the battery cell.

[0005] In summary, developing a simpler method to construct a gel polymer electrolyte and a stable and elastic SEI film layer is of great significance for extending the life of the battery cell and improving the safety of the battery cell. In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a gel battery cell, which is used to solve the defect of introducing toxic initiators when preparing gel electrolytes by in-situ polymerization on the one hand, and on the other hand to solve the defect that the SEI film formed by conventional electrolyte additives is highly rigid and cannot adapt to the volume change during battery cycles; in addition, it has good performance in solving technical problems in electrochemical performance such as poor stability of the negative electrode interface of the battery cell, serious side reactions on the electrode surface, uneven ion deposition, and leakage or volatilization of the liquid electrolyte.

[0007] The second purpose of the present invention is to provide a method for preparing the gel battery cell, which is simple, easy, non-toxic and safe; the unsaturated double bond monomer and the cross-linking agent are anion polymerized in situ under the initiation of the negative electrode, and no additional toxic or harmful initiator needs to be added, which simplifies the preparation method of the gel battery cell and can meet the needs of mass production.

[0008] The third object of the present invention is to provide a secondary battery having good electrochemical performance and service life while solving the above technical problems.

[0009] The fourth object of the present invention is to provide an electrical device having the same technical advantages as the gel battery and the secondary battery.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A gel battery cell comprises a positive electrode, a negative electrode and a gel polymer electrolyte, wherein the gel polymer electrolyte comprises a polymer and an electrolyte;

[0012] Wherein, the polymer is prepared by in-situ polymerization of an electron-deficient double-bond monomer and a cross-linking agent on the surface of the negative electrode;

[0013] The electron-deficient double bond monomer includes a compound as shown in structure (I):

[0014] X includes one of trifluoromethyl, cyano, fluorine, chlorine or bromine atoms, and R includes a hydrogen atom or C x H y , x is any integer from 1 to 5, and y=2x+1.

[0015] A method for preparing the gel battery cell comprises the following steps:

[0016] A mixed solution comprising an electron-deficient double-bond monomer, a cross-linking agent and an electrolyte is prepared, and the mixed solution is injected into a dry battery cell comprising a positive electrode and a negative electrode, and the mixture is packaged and allowed to stand to obtain a gel battery cell.

[0017] A secondary battery comprises the gel battery cell.

[0018] An electrical device comprises the gel battery cell.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The gel cell provided by the present invention uses electron-deficient double-bond monomers to initiate anionic polymerization on the negative electrode surface. The negative electrode surface film layer formed by the polymer obtained by polymerization can protect the negative electrode interface and prevent the electrolyte from decomposing on the negative electrode surface. At the same time, it assists in forming a stable inner inorganic SEI layer, promotes the uniform deposition of lithium ions, and improves the rate performance of the cell. At the same time, anionic polymerization proceeds from the negative electrode to the positive electrode, and the polymer further combines with the electrolyte to form a gel polymer electrolyte, which fixes the electrolyte in the polymer network, reduces the interface movement of the electrolyte, reduces the interface side reactions, and prolongs the service life of the cell; and the gel polymer electrolyte can also reduce the leakage and volatilization of the electrolyte, thereby improving the safety of the cell.

[0021] (2) The preparation method of the gel battery provided by the present invention can increase the interface contact between the electrolyte and the electrode, reduce the interface contact impedance, accelerate the transfer of ions at the interface, and improve the rate performance of the battery. At room temperature and 2C current density, the capacity retention rate is increased by 5.9%. At the same time, the flexible polymer film layer formed on the negative electrode surface by in-situ anionic polymerization can adapt to the huge volume expansion of the negative electrode during the cycle, ensure the integrity of the SEI layer at the negative electrode interface, reduce interface side reactions, and improve the cycle stability of the battery. The capacity retention rate of 200 cycles reaches up to 96%, an increase of 11.8%. DETAILED DESCRIPTION

[0022] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.

[0023] The first aspect of the present invention is to provide a gel battery cell, comprising a positive electrode, a negative electrode and a gel polymer electrolyte, wherein the gel polymer electrolyte comprises a polymer and an electrolyte; wherein the polymer is prepared by in-situ polymerization of an electron-deficient double bond monomer and a cross-linking agent on the surface of the negative electrode, and the electrolyte is fixed in a gel network structure formed by the polymer; the electron-deficient double bond monomer comprises a compound as shown in structure (I):

[0024] X includes one of trifluoromethyl, cyano, fluorine, chlorine or bromine atoms, and R includes a hydrogen atom or C a H b , a is any integer from 1 to 5, and b=2a+1.

[0025] As a preferred embodiment, the cross-linking agent includes a compound as shown in structure (II):

[0026] Y includes a trifluoromethyl group, a cyano group or a fluorine atom, and n is any integer from 1 to 10.

[0027] It can be understood that in the gel battery cell of the present invention, based on the reaction mechanism of the in-situ polymerization, on the one hand, a polymer film layer obtained by in-situ polymerization is loaded on the surface of the negative electrode, and on the other hand, the gel polymer electrolyte is formed, and the electrolyte is fixed in the network of the gel polymer electrolyte.

[0028] The electron-deficient double bond monomer and the cross-linking agent used in the present invention both have directly connected electron-withdrawing groups on the double bonds; due to the strong electron-withdrawing effect of the adjacent electron-withdrawing groups, the electrons on the double bonds are attracted by the electron-withdrawing groups, resulting in the double bonds being in an electron-deficient state, which is easily attacked by the lone pair of electrons of the Lewis base or the electrons donated by the metal and the metal-carbon composite material to form carbon anions, thereby initiating anionic polymerization of the monomers; therefore, in the present invention, there is no need to add an additional initiator to initiate the polymerization of the monomers, which can effectively simplify the preparation process of the gel electrolyte.

[0029] It can also be understood that since the polymerization is initiated by the negative electrode and forms a dense polymer film layer on the surface of the negative electrode, the polymer film layer further reacts with the negative electrode to form a LiF, Li x The inorganic SEI film layer of N realizes the stability of the negative electrode interface, while promoting the transfer of ions at the interface and reducing the interface ion transfer impedance; thus, the polymer film layer and the inorganic film layer jointly form a stable organic-inorganic interface at the negative electrode interface, thereby improving the safety and cycle stability of the battery cell.

[0030] As a preferred embodiment, the negative electrode comprises a metal negative electrode or a metal-carbon material negative electrode. In the present invention, the electron-deficient double bond monomer can be anion polymerized by trace water in the negative electrode or electrolyte to form the gel polymer electrolyte in situ.

[0031] As a more preferred embodiment, the metal negative electrode includes at least one of lithium, sodium, and potassium; the metal-carbon material negative electrode refers to a carbon negative electrode material that can embed metal ions and form a metal-carbon material during the operation of the battery. Specifically, the carbon negative electrode material of the lithium battery and the potassium battery can adopt a graphite negative electrode, and the potassium battery can also select soft carbon as the carbon negative electrode material, and the sodium battery can select hard carbon as the carbon negative electrode material.

[0032] As a preferred embodiment, the electron-deficient double bond monomer includes at least one of methyl 2-cyanoacrylate, ethyl 2-cyanoacrylate, butyl 2-cyanoacrylate, methyl 2-(trifluoromethyl)acrylate, 2-(trifluoromethyl)acrylic acid, 2-fluoroacrylic acid, methyl 2-fluoroacrylate, 2-chloroacrylic acid, methyl 2-chloroacrylate, 2-bromoacrylic acid or methyl 2-bromoacrylate; in some more preferred embodiments, the electron-deficient double bond monomer is methyl 2-(trifluoromethyl)acrylate.

[0033] In the present invention, for the structure of the electron-deficient double bond monomer, when X is selected from trifluoromethyl or fluorine atom, the effect achieved is relatively better than that of chlorine atom or bromine atom, and generally the effect of fluorine, chlorine, bromine and iodine decreases; therefore, it is more preferred that X is the electron-deficient double bond monomer corresponding to trifluoromethyl, cyano or fluorine atom.

[0034] As a preferred embodiment, the molecular weight of the cross-linking agent is 300-1200, including but not limited to any one of 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200 or a numerical range consisting of any two thereof.

[0035] As a preferred embodiment, the cross-linking agent includes at least one of polyethylene glycol 2-(trifluoromethyl)acrylate, polyethylene glycol 2-cyanoacrylate, and polyethylene glycol 2-fluoroacrylate.

[0036] As a more preferred embodiment, the cross-linking agent is obtained by an ester exchange reaction between an acrylic acid ester compound and polyethylene glycol in an anhydrous solvent; in a further preferred embodiment, the anhydrous solvent includes but is not limited to acetonitrile, tetrahydrofuran, toluene, N-methylpyrrolidone, etc.; in a further preferred embodiment, the reflux temperature of the ester exchange reaction is 80°C to 120°C, and the reflux time is 4h to 24h.

[0037] As a preferred embodiment, the present invention does not impose any restrictions on the types of the positive electrode and the electrolyte; those skilled in the art can select the types of the positive electrode and the electrolyte based on the requirements for battery types such as lithium batteries, sodium batteries or potassium batteries.

[0038] The second aspect of the present invention is to provide a method for preparing the gel battery cell, which mainly comprises the following steps: preparing a mixed solution comprising an electron-deficient double bond monomer, a cross-linking agent and an electrolyte, injecting the mixed solution into a dry battery cell comprising a positive electrode and a negative electrode, encapsulating and allowing to stand, and obtaining a gel battery cell.

[0039] As described in the first aspect of the present invention, in the preparation method of the present invention, there is no need to add additional initiating functional compounds, and the initiation conditions of the in-situ polymerization reaction of the electron-deficient double bond monomer are determined according to the negative electrode material in the battery cell; when the negative electrode is a pure metal, it is directly initiated by the corresponding metal negative electrode; when the negative electrode is a carbon material, it is initiated by the negative electrode metal and carbon formed during the formation and capacity separation of the battery cell to form a corresponding metal-carbon material complex.

[0040] As a preferred embodiment, the preparation method is carried out in a dry environment (low humidity environment, air humidity <2% RH); at the same time, the mixed liquid should reduce contact with air during the preparation and injection process, and the injection operation should be carried out as quickly as possible.

[0041] As a preferred embodiment, the mixed liquid is prepared in an inert atmosphere, which includes but is not limited to nitrogen, helium, neon, argon, and the like.

[0042] As a preferred implementation manner, the standing time is 20 hours to 30 hours.

[0043] As a preferred embodiment, the mass ratio of the electron-deficient double bond monomer to the cross-linking agent is (70-97): (3-30), and in some more preferred embodiments the mass ratio is (85-90): (10-15); specifically including but not limited to the ratio interval composed of ratios such as 70:30, 75:25, 80:20, 85:15, 87:13, and 90:10.

[0044] As a preferred embodiment, the ratio of the sum of the masses of the electron-deficient double bond monomer and the cross-linking agent to the mass of the electrolyte is 2% to 50%. In some more preferred embodiments, the mass ratio is 5% to 8%, specifically including but not limited to the range interval consisting of 2%, 5%, 6%, 7%, 8%, 10%, 20%, 25%, 30%, 40%, 50% and the like.

[0045] As a preferred embodiment, for button batteries or small battery devices for testing, the mixed solution is added to the diaphragm, and the diaphragm containing the mixed solution is added to the dry cell, and then packaged, left to stand, and a gel cell is obtained; or, for large battery devices that require winding or lamination, a dry cell containing a diaphragm and an electrode structure is prepared in advance, and then the mixed solution is injected, and then packaged, left to stand, and a gel cell is obtained. Those skilled in the art can optimize the specific implementation steps without violating the preparation method provided by the present invention.

[0046] The third aspect of the present invention is to provide a secondary battery, including the gel cell. The secondary battery includes but is not limited to a lithium battery, a sodium battery, a potassium battery, a magnesium battery or a multi-metal battery, etc.; the secondary battery of the present invention may also selectively include other necessary or unnecessary functional elements or packaging components, etc., which can be arbitrarily selected and combined by those skilled in the art; when the gel cell of the present invention is included in the secondary battery, it can be regarded as an embodiment of the present invention.

[0047] The fourth aspect of the present invention is to provide an electrical device, including the gel battery. The electrical device includes but is not limited to electric vehicles, electronic products, energy storage devices for energy storage projects, etc. When the gel battery is included, any electrical device equipped with the gel battery can belong to an embodiment of the present invention.

[0048] Example 1

[0049] 0.09 g polyethylene glycol di(trifluoromethyl)acrylate (M n =300), 0.51g of methyl 2-(trifluoromethyl)acrylate was added to 9.40g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial diaphragm, and assembled into a button cell with a lithium metal negative electrode and a ternary nickel-cobalt-manganese-lithium. The cell was allowed to stand at room temperature for 12h to obtain the in-situ anionic polymerization gel cell of this embodiment.

[0050] The commercial electrolyte involved in each embodiment of the present invention is: 1 mol / L LiPF6-EC / DMC / DEC (v / v / v=1:1:1); the molecular formula of the ternary nickel-cobalt-manganese-lithium is: LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811); commercial diaphragms are all commercial alumina-coated PE diaphragms.

[0051] Example 2

[0052] 0.15 g of ethylene glycol dicyanoacrylate (M n=300), 4.85 g of methyl 2-cyanoacrylate was added to 5.00 g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial diaphragm, and assembled into a button cell with a lithium metal negative electrode and a ternary nickel-cobalt-manganese-lithium. The cell was allowed to stand at room temperature for 12 h to obtain the in-situ anionic polymerization gel cell of this embodiment.

[0053] Example 3

[0054] 0.06 g of ethylene glycol di-2-fluoroacrylate (M n =1200), 0.14 g of methyl 2-fluoroacrylate was added to 9.80 g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial separator, and assembled into a button cell with a lithium metal negative electrode and a ternary nickel-cobalt-manganese-lithium. The cell was allowed to stand at room temperature for 12 h to obtain the in-situ anionic polymerization gel cell of this embodiment.

[0055] Example 4

[0056] 0.09 g of ethylene glycol di-2-fluoroacrylate (M n =600), 0.31g of trifluoromethylacrylic acid and 0.20g of ethyl 2-cyanoacrylate were added to 9.40g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial diaphragm, and assembled into a button cell with a lithium metal negative electrode and a ternary nickel-cobalt-manganese-lithium. The cell was allowed to stand at room temperature for 12h to obtain the in-situ anionic polymerization gel cell of this embodiment.

[0057] Example 5

[0058] 0.09 g of ethylene glycol di(trifluoromethyl)acrylate (M n =300), 0.51g of butyl 2-cyanoacrylate was added to 9.40g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial diaphragm, and assembled into a button cell with a lithium metal negative electrode and a ternary nickel-cobalt-manganese-lithium. The cell was allowed to stand at room temperature for 12h to obtain the in-situ anionic polymerization gel cell of this embodiment.

[0059] Comparative Example 1

[0060] 9.40 g of commercial electrolyte was dropped onto the commercial separator, assembled into a button cell with a lithium metal negative electrode and a ternary nickel-cobalt-manganese-lithium, and allowed to stand at room temperature for 12 h to obtain a conventional liquid battery cell of this comparative example.

[0061] Comparative Example 2

[0062] 0.09 g of polyethylene glycol diacrylate (M n=300), 0.51g of 2-methoxyethyl acrylate and 0.006g of azobisisobutyronitrile were added to 9.80g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial diaphragm, and assembled into a button cell with a lithium metal negative electrode and a ternary nickel-cobalt-manganese-lithium battery, which was heated at 65°C for 10 hours to obtain an in-situ free radical polymerized gel battery cell.

[0063] Test Example 1

[0064] The cell cycle performance of each embodiment and comparative example was tested between 2.5V and 4.25V, the cell rate performance was tested at 0.5C, 1C, and 2C current densities, and the capacity ratio at 2C rate to 0.33C base rate was tested; in addition, the cell cycle performance was tested at 0.5C / 1C. The test results are shown in Table 1.

[0065] Table 1

[0066] 2C capacity retention rate (0.33C) 200 cycles capacity retention Example 1 94% 92% Example 2 84% 93% Example 3 92% 87% Example 4 96% 95% Example 5 87% 87% Comparative Example 1 89% 85% Comparative Example 2 82% 86%

[0067] Example 6

[0068] 0.08 g of ethylene glycol dicyanoacrylate and 0.72 g of methyl 2-(trifluoromethyl)acrylate were added to 9.2 g of commercial electrolyte, mixed evenly to obtain a precursor solution, and the obtained precursor solution was injected into a 3.28 Ah graphite||NCM811 dry battery cell, allowed to stand at room temperature for 10 h, and then charged to 3.2 V at 0.02 C at 45 ° C, and then charged to 3.75 V at 0.05 C, and then transferred to room temperature and allowed to stand for 10 h to obtain the in situ anionic polymerization gel battery cell of this embodiment.

[0069] Comparative Example 3

[0070] 9.2 g of commercial electrolyte was injected into a 3.28 Ah graphite||NCM811 dry battery cell, left standing at room temperature for 10 h, then charged to 3.2 V at 0.02 C at 45 ° C, and then charged to 3.75 V at 0.05 C, and then returned to room temperature and left standing for another 10 h to obtain a conventional liquid battery cell of this comparative example.

[0071] Test Example 2

[0072] The electrochemical performance and safety performance of the battery cells of Example 7 and Comparative Example 3 were tested between 2.5V and 4.25V. The DC internal resistance at 25°C@50% SOC and the capacity retention rate after 500 cycles of charge and discharge were tested respectively; the safety performance test was carried out by a 100% SOC vertical needle puncture test. The test results are shown in Table 2.

[0073] Table 2

[0074] Example 6 Comparative Example 3 DC internal resistance / Ω 10.2 11.0 Capacity retention rate 92% 81% Acupuncture experiment No smoke, no fire Severe heat rise, fire

[0075] Example 7

[0076] 0.09 g of ethylene glycol di(trifluoromethyl)acrylate (M n =300), 0.51g of methyl 2-(trifluoromethyl)acrylate was added to 9.40g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial diaphragm, and assembled into a button cell with a sodium metal negative electrode and a Na3V2(PO4)3 positive electrode. The cell was allowed to stand at room temperature for 12h to obtain the in-situ anionic polymerization gel cell of this embodiment.

[0077] Example 8

[0078] 0.09 g of ethylene glycol di(trifluoromethyl)acrylate (M n =300), 0.51 g of methyl 2-(trifluoromethyl)acrylate was added to 9.40 g of commercial electrolyte, and the mixture was evenly mixed to obtain a precursor solution. The obtained precursor solution was dropped onto a commercial diaphragm, and assembled into a button cell with a potassium metal negative electrode and K2MnFe(CN)6. The cell was allowed to stand at room temperature for 12 h to obtain the in-situ anionic polymerization gel cell of this embodiment.

[0079] Test Example 3

[0080] The gel cell prepared in Example 8 was tested for cell cycle performance between 2.3 V and 3.9 V, and 0.33 C showed a performance of 116 mAh·g -1 At the same time, the gel battery prepared in Example 9 was tested for battery cycle performance between 2.5V and 4.6V, and 0.33C showed 135mAh·g -1 Specific capacity.

[0081] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A gel battery cell, characterized in that: The gel battery cell comprises a positive electrode, a negative electrode and a gel polymer electrolyte, wherein the gel polymer electrolyte comprises a polymer and an electrolyte; Wherein, the polymer is prepared by in-situ polymerization of an electron-deficient double-bond monomer and a cross-linking agent on the surface of the negative electrode; The electron-deficient double bond monomer includes a compound as shown in structure (I): X includes one of trifluoromethyl, cyano, fluorine, chlorine or bromine atoms, and R includes a hydrogen atom or C x H y , x is any integer from 1 to 5, and y=2x+1.

2. The gel battery cell according to claim 1, characterized in that: The cross-linking agent includes a compound as shown in structure (II): Y includes one of trifluoromethyl, cyano or fluorine atom, and n is any integer from 1 to 10; Preferably, the cross-linking agent includes at least one of polyethylene glycol 2-(trifluoromethyl)acrylate, polyethylene glycol 2-cyanoacrylate, and polyethylene glycol 2-fluoroacrylate.

3. The gel battery according to claim 1, characterized in that: The negative electrode includes a metal negative electrode or a metal-carbon material negative electrode.

4. The gel battery cell according to claim 1, characterized in that: The electron-deficient double bond monomer includes at least one of methyl 2-cyanoacrylate, ethyl 2-cyanoacrylate, butyl 2-cyanoacrylate, methyl 2-(trifluoromethyl)acrylate, 2-(trifluoromethyl)acrylic acid, 2-fluoroacrylic acid or methyl 2-fluoroacrylate, 2-chloroacrylic acid, methyl 2-chloroacrylate, 2-bromoacrylic acid or methyl 2-bromoacrylate.

5. The method for preparing a gel battery cell according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: A mixed solution comprising an electron-deficient double-bond monomer, a cross-linking agent and an electrolyte is prepared, and the mixed solution is injected into a dry battery cell comprising a positive electrode and a negative electrode, and the mixture is packaged and allowed to stand to obtain a gel battery cell.

6. The method for preparing the gel battery according to claim 5, characterized in that: The mass ratio of the electron-deficient double bond monomer to the cross-linking agent is (70-97): (3-30).

7. The method for preparing the gel battery according to claim 5, characterized in that: The ratio of the sum of the mass of the electron-deficient double-bond monomer and the cross-linking agent to the mass of the electrolyte is 2% to 50%.

8. The method for preparing the gel battery according to claim 5, characterized in that: The mixed solution is prepared in an inert gas atmosphere; and / or the preparation method is carried out in a dry atmosphere.

9. A secondary battery, characterized in that: It comprises the gel battery cell as claimed in any one of claims 1 to 4.

10. An electrical device, characterized in that: The invention comprises the gel battery cell as claimed in any one of claims 1 to 4.

Citation Information

Patent Citations

  • In-situ heat cross bonding process for preparing fluorine containing gel state electrolyte material and process for making polymeric lithium ion cell

    CN1558463A

  • Alkali metal electrode treatment agent, electrolytic solution for alkali metal secondary battery, alkali metal electrode, alkali metal secondary battery, and module

    US20220311050A1

  • Gel polymer electrolytes, and energy-storage cells and batteries made therewith

    WO2024119495A1

Cited By

  • Fluorinated gel electrolyte with wide temperature range and high specific energy as well as preparation method and application of fluorinated gel electrolyte

    CN121507085A